Primary central nervous system lymphoma in an immunocompetent patient. Case report - Loría Avila, Esteban (2015)
Primary central nervous system non-Hodgkin's lymphoma (PCNSL) is a rare form of non-hodgkig lymphoma (NHL) characterized by the presence of injuries to the CNS and no evidence of a primary tumor in the initial diagnosis. Objectives: To describe a PCNSL case and to do a bibliographical review on the subject. The patient is a 56 year old immunocompetent woman, who consulted the doctor about a confusional syndrome. Whole body CAT scan only showed two brain injuries. A B-cell NHL was found after the tumor´sbiopsy, and therefore the DeAngelis protocol was started; the results obtained were satisfactory.